Concerning Identification of the Non-Economic Process - Lulanski, Pano (Research Papers, 2005)
The paper determines two types of activities (material and ideationally-transformational) which serve as the context to look into the nature and character of the non-economic process.Its main features and its institutional structure are reviewed and summarized. A consistent attempt is made to differentiate between economy and economics, as well as economy and noneconomic process in the context of the unity between production and consumption on the one hand, and in terms of the existing effect of different historical circumstances on them, on the other hand.The paper examines the operational and structural boundaries of the non-economic process in its social and economic form . Some practical solutions of the matter under review have been researched.